Gender Differences in English Vowel Production by Pashto Speakers - Biland, Sawera; Irshad, Asra (Pakistan Languages and Humanities Review, 2025)
This study explores gender-based differences in the production of six English vowels—/iː/, /ɪ/, /æ/, /ɑː/, /ʌ/, and /uː/—by native Pashto speakers. It aims to analyze the acoustic characteristics of these vowels and assess whether typical vowel contrasts are distinctly produced. Recognizing the phonological differences between Pashto and English, and physiological gender-based speech variations, this research applies a quantitative approach to assess vowel production patterns. Ten undergraduate students from the University of Buner uttered a minimal pair word list three times. Their utterances were recorded and analyzed using Praat software, focusing on vowel duration and the first two formants (F1 and F2). Quantitative data analysis revealed that male speakers produced longer vowels with lower formants, while female speakers showed shorter durations and higher F1 and F2 values. Despite these differences, both groups maintained clear vowel distinctions. It is recommended to examine the pronunciation of English diphthongs by Pashto speakers in order to identify and analyze the specific challenges they encounter.